2023
DOI: 10.1177/03635465231158372
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Assessment Tool Based on Scapular Y-View for Global Fatty Infiltration in the Supraspinatus Muscle: Correlation, Predictive Performance, and Reliability Analyses

Abstract: Background: The accurate evaluation of rotator cuff (RC) fatty degeneration after tears is critical for appropriate surgical decision making and prognosis. However, there is currently no reliable and practical tool to reflect the global fatty infiltration (Global-FI) throughout the 3-dimensional (3D) volumetric RC muscles. Purpose: (1) To determine the correlations between 2 modified assessment tools and the Global-FI and their predictive performances and reliabilities for Global-FI prediction, and (2) to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 45 publications
(94 reference statements)
0
10
1
Order By: Relevance
“…2-C) to calculate the 3D muscle and intramuscular fat volumes. The 3D FI was calculated as the percentage of intramuscular fat volume to total muscle volume 1,9,11,21,22 . This 3D measurement method has been reported to have good intra- and interobserver reliabilities 9 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…2-C) to calculate the 3D muscle and intramuscular fat volumes. The 3D FI was calculated as the percentage of intramuscular fat volume to total muscle volume 1,9,11,21,22 . This 3D measurement method has been reported to have good intra- and interobserver reliabilities 9 .…”
Section: Methodsmentioning
confidence: 99%
“…2-A), a semiautomatic segmentation program (www.itksnap.org), to stack and integrate all images for 3D reconstruction according to the reported methods in previous studies (Fig. 2-B) 9,21,22 . The 3D models of the supraspinatus muscle and fat were automatically reconstructed from all 2D binary images (Fig.…”
Section: D Supraspinatus Volume and Fi Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Single-slice measurements in 2-dimensional (2D) Y-views are appealing, especially in the clinical setting, but, as intramuscular fat distribution is inhomogeneous [33][34][35] , the measurements hardly correlate with the global 3D FF 28,33,[36][37][38] . For this reason, Xu et al proposed a modified assessment tool 39 consisting of the mean of 3 FF measurements on 6-point Dixon sagittal images: the scapular Y-view and 2 adjacent slices. They showed that this mean FF correlates strongly with the 3D volumetric global FF of the entire supraspinatus (SSP) muscle 39 .…”
mentioning
confidence: 99%